2004
DOI: 10.1152/ajpendo.00445.2003
|View full text |Cite
|
Sign up to set email alerts
|

Islet cell engraftment and control of diabetes in rats after transplantation of pig pancreatic anlagen

Abstract: The insufficient supply of tissue, loss posttransplantation, and limited potential for expansion of beta-cells restrict the use of islet allotransplantation for diabetes. A way to overcome the supply and expansion problems is to xenotransplant embryonic tissue. We have shown that whole rat pancreatic anlagen isotransplanted into the omentum of rats, or xenotransplanted into costimulatory blocked mice, undergo growth and differentiate into islets surrounded by stoma without exocrine tissue. Isotransplants norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
5
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(111 citation statements)
references
References 24 publications
5
100
5
1
Order By: Relevance
“…However, the immune suppression required to maintain the implants was either too toxic or included anti-CD40L, which cannot be used in human patients due to its thrombotic properties. Other studies suggested that E28 pancreatic tissue might be accepted in nonimmunosuppressed rats (33) and monkeys (34). In contrast, our mouse (9) and rat (35) data has revealed fierce rejection of pig embryonic tissue of any gestational time point in the absence of immune suppression, while demonstrating that the immunogenicity of E42 tissue was relatively lower compared to tissues harvested at E56 or beyond (9).…”
Section: Discussioncontrasting
confidence: 63%
“…However, the immune suppression required to maintain the implants was either too toxic or included anti-CD40L, which cannot be used in human patients due to its thrombotic properties. Other studies suggested that E28 pancreatic tissue might be accepted in nonimmunosuppressed rats (33) and monkeys (34). In contrast, our mouse (9) and rat (35) data has revealed fierce rejection of pig embryonic tissue of any gestational time point in the absence of immune suppression, while demonstrating that the immunogenicity of E42 tissue was relatively lower compared to tissues harvested at E56 or beyond (9).…”
Section: Discussioncontrasting
confidence: 63%
“…Among them are such widespread diseases as diabetes, end-stage renal disease, Parkinson's disease, acute and chronic liver failure, and inherited metabolic disorders. The efficacy of committed embryonic pig or human kidney (13,28), pancreas (29)(30)(31)(32)(33)(34), lung (35), heart, or intestine (35,36) as well as hepatocytes (37)(38)(39)(40) or neuronal precursors (41)(42)(43), which grew and differentiated upon implantation into SCID or nude mice or rats, has been extensively Embryonic pig pancreas tissues obtained at various gestational ages were implanted under the kidney capsule. Tissue growth and serum levels of pig insulin were evaluated 6 weeks after implantation as described in Methods.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38] No matter whether dispersed or intact developing pancreas is transplanted, there is a selective survival of the endocrine portion (islets) of pancreatic anlagen grafts. In studies that compared directly, host beta cell mass post-transplantation of whole versus digested pancreas, it was found that mass was larger if whole pancreas were transplanted.…”
Section: Organogenesis Of the Endocrine Pancreasmentioning
confidence: 99%
“…30 We have transplanted pancreatic anlagen from embryos into the peritoneal membranes of rodents using techniques developed for the transplantation of metanephroi. 35,36 Rat to Rat Isotransplantation. Shown in Figure 7A is a photograph of a section of duodenum (duo) from an E12.5 Lewis rat embryo.…”
Section: Organogenesis Of the Endocrine Pancreasmentioning
confidence: 99%
See 1 more Smart Citation